2005
DOI: 10.1007/s00464-004-8221-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ablation of the gallbladder

Abstract: Minicholecystostomy followed by chemical ablation of the gallbladder was a safe, effective, and simple procedure for treating high-risk patients with acute cholecystitis and/or cholelithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Historically, there have been several studies that have investigated the feasibility of gallbladder ablation in animal models and human cholecystitis patients with various chemical agents, such as acetic acid, alcohol, and sodium hypochlorite as well as heat and laser modalities, occasionally with pre-ablation cystic duct embolization. 27 28 29 30 31 32 Some of these studies have demonstrated success, however, issues included ineffective or incomplete mucosal ablation, mucocele formation, requirement for several ablation sessions, and mucosal regeneration. 33 To our knowledge, the only multi-patient study over the last decade to investigate gallbladder chemical ablation is a prospective study of 10 acute cholecystitis patients performed recently by Atar et al 32 Patients first underwent percutaneous cholecystostomy tube replacement followed by clearance of existing bile duct stones into the duodenum before undergoing cystic duct embolization with coils.…”
Section: Gallbladder Ablationmentioning
confidence: 99%
“…Historically, there have been several studies that have investigated the feasibility of gallbladder ablation in animal models and human cholecystitis patients with various chemical agents, such as acetic acid, alcohol, and sodium hypochlorite as well as heat and laser modalities, occasionally with pre-ablation cystic duct embolization. 27 28 29 30 31 32 Some of these studies have demonstrated success, however, issues included ineffective or incomplete mucosal ablation, mucocele formation, requirement for several ablation sessions, and mucosal regeneration. 33 To our knowledge, the only multi-patient study over the last decade to investigate gallbladder chemical ablation is a prospective study of 10 acute cholecystitis patients performed recently by Atar et al 32 Patients first underwent percutaneous cholecystostomy tube replacement followed by clearance of existing bile duct stones into the duodenum before undergoing cystic duct embolization with coils.…”
Section: Gallbladder Ablationmentioning
confidence: 99%
“…Becker et al showed the feasibility of ablation in a porcine model using electrocoagulation for cystic duct ablation, and repeated cycles of 95% EtOH and 3% STS to ablate the gallbladder, subsequently attempted in 8 patients [4,6]. A second series of 34 patients treated similarly had limited success [9]. Boiling contrast (76% diatrizoate meglumine and sodium) and catheter-based thermoablation of the gallbladder had limited success [8].…”
mentioning
confidence: 96%
“…Clinical Findings/Procedure Details: Early chemical sclerosing agents attempted in animal gallbladders included EtOH, 3% sodium tetradecyl sulfate (STS), tetracycline, trifluoroacetic acid, NaOH, hydrogen peroxide, phenol, methyl cyanoacrylate, morrhuate sodium solution, and sodium carbonate. Complications included spillage of sclerosing agent, gallbladder rupture, incomplete ablation, and abscess/mucocele formation [9][10]. Becker et al showed the feasibility of ablation in a porcine model using electrocoagulation for cystic duct ablation, and repeated cycles of 95% EtOH and 3% STS to ablate the gallbladder, subsequently attempted in 8 patients [4,6].…”
mentioning
confidence: 99%